Measuring Participants’ Satisfaction of “Sekolah Orang Tua” Using Service Quality Method in The Healthy and Non-additives Food Making Course - Budiyono Saputro (Al Hikmah: Jurnal Studi Keislaman, 2020)
Abstract: This research aimed to satisfaction response of student’s parents/guardians who join “Sekolah Orang Tua” (literally: Parent School) of Integrated Islamic Early Childhood Education Zaid Bin Tsabit Ambartawang, Yayasan Pendidikan Al-Qur’an Sirojudin Ikhsan, Mungkid District, Magelang Regency, Indonesia to The Healthy and non-Additives food Making Course in the form of preservative-free banana nugget and sugar-free infused fruit water which is adjusted to local fruits. This satisfaction response can be measured using Service Quality (Servqual) method. The research results indicate that in Responsiveness and Empathy dimensions, no decrease is found between perception and expectation, hence they have positive (+) sign. It means the student’s parents/guardians show satisfaction response. For Tangibles, Reliability, and Assurance dimensions, decreases are found between perception and expectation, leading to them getting negative (-) signs. This dissatisfaction response shall be the benchmarks for instructors in the course to refine the dimensions and their supporting attributes such as: (1) content, (2) tools, materials and media, (3) venue of event, and (4) appropriate and effective duration of event. Keywords: parents school, satisfaction response, service quality method.